IMPACT OF VIRAL MYOCARDITIS ON THE COURSE OF PREGNANCY AND DELIVERY - Eshonkhodjaeva, D.Dj.; Babadjanova, G.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background: COVID-19 is mainly a respiratory infection; however, in some cases, it can result in cardiac complications in pregnant women leading to the development of myocarditis. We studied the impact of COVID-19-associated myocarditis on the course of pregnancy in the Republican Perinatal Center (Tashkent, Republic of Uzbekistan). Material and methods: We examined a total of 147 pregnant women with myocarditis (of them, 95 women had COVID-19 while pregnant and 52 women had chronic focal myocarditis). The patients underwent electrocardiography, echocardiography, ultrasonography, and laboratory studies (troponin T1). Results: In pregnant women with COVID-19, associated myocarditis develops mainly 2-3 weeks after COVID-19, characterized by the development of circulatory insufficiency. On the Echo-kardiogram, metabolic changes were more typical for pregnant women in group 1 with covid-associated myocarditis compared with pregnant women with sluggish focal myocarditis, however, pathological changes were detected more in group 2, which indicates more pronounced myocardial changes in pregnant women in group 2 with chronic focal myocarditis. Conclusion: Doppler measurements of blood flow in the vessels of the fetoplacental complex of pregnant women of group 1 who had COVID-19 revealed predominantly a violation of fetal-placental blood flow, one of the reasons for which.